The Relationship Between Parental Parenting And Nutritional Status In Toddlers - Efi Satriana Silalahi (International Archives of Medical Sciences and Public Health, 2022)
Introduction: In developing countries, pain and mortality in children under five are largely influenced by nutrition, so the morbidity and mortality rates in this period can be useful information about malnutrition in society. Childcare can be defined as the behaviour practised by caregivers (mother, father, grandmother, caregiver) in providing food, health maintenance, stimulation and emotional support needed by children for growth and development, including parental affection and responsibility. This study aimed to determine whether there was a relationship between parental parenting and the state of nutritional status in toddlers. Method: This type of research is analytical research with a cross-sectional approach. The population in this study was all mothers who had toddlers in Hamlet XX Bandar Klippa Village, Percut Sei Tuan District, which amounted to 75 people (total sampling). Data were obtained by interview using questionnaires. The results of the chi-square statistical test have a value of p = 0.011 < 0.05. Result : The results of this study show that parental parenting is very influential on the nutritional status of toddlers. Still found toddlers with nutritional status in the underweight category of 20.0%, short category height of 40.0% and nutritional status of the thin category of 11.4%.It is recommended to every parent to pay more attention to actions and parenting patterns in eating, basic care, as well as sanitation and the environment so that it will able to improve the nutritional status of toddlers.